Preparation of c-axis textured SiC ceramics by a strong magnetic field of 6 T assisted gel-casting process. Issue 5 (April 2016) - Yang, Zhigang; Yu, Jianbo; Ren, Zhongming; Deng, Kang; Li, Chuanjun; Zhong, Yunbo; Wang, Qiuliang; Dai, Yinming; Wang, Hui
Abstract: C -axis textured SiC ceramics were prepared by a strong magnetic field of 6 T assisted gel-casting and subsequent pressureless sintering. The optimal suspension parameters for gel-casting were determined by analyzing the influences of pH value and dispersant content on the stability and dispersibility of suspensions. The effect of sintering conditions on the texture development and properties of SiC ceramics was discussed. It was found that the increasing sintering temperature or holding time promoted the densification process of SiC ceramics. The c -axis of SiC grain was aligned parallel to the magnetic field by applying a strong magnetic field of 6 T. The degree of texture of SiC ceramics showed a slightly increasing trend with the increase of sintering temperature or holding time. When the samples were sintered at 1950 °C for 4 h or 6 h, the large elongated grains were formed in the samples, leading to the extremely evident anisotropic microstructure on different planes. Textured SiC ceramics exhibited the anisotropic bending strength.